O processo avaliativo da aprendizagem na Escola Mun. Antonio F. dos Santos localizada na comunidade Ribeirão Grande I (Pedro Bento) no município de Tocantinópolis-TO - Silva, Santana Santos (Universidade Federal do Tocantins, 2022)
This study has the objective of comprehending the evaluation process of a mixed grade classroom from the municipal school Antonio Fernandes dos Santos in the Community of Ribeirão Grande I (Pedro Bento) in the city of Tocantinópolis-TO, considering the perception of the student’s parents and the school’s teachers. In face of this research context, some questions were proposed: What are the possibilities and the difficulties faced by the students and by the teachers considering the evaluation process? What are the parents’ and teachers’ perceptions regarding the evaluation steps used in the municipal school Antonio Fernandes dos Santos? Considering this, the following research is characterized as a Case Study, with a qualitative approach and an exploratory nature, also presenting a documental and bibliographical review. As our tool for data collection, we used a questionnaire that was applied to two teachers from the school and to the student’s parents. This investigation showed us that the evaluation tools used in this school are quite diversified, mixing characteristics from the traditional approach (classificatory) and the emancipatory approach. A teacher that answered the questionnaire creates her evaluations according to the difficulties and the development of each student, presenting the students with the needed support to overcome their difficulties. Another teacher plans her classes based on the curricular grade, with didactics materials directed to urban teaching, which can cause many learning challenges. Another result concerns the obstacles faced by some teachers when planning their classes due to a lack of specific materials for rural teaching; absence of pedagogical support; lack of collaboration between the parents and the school and with the teaching that is offered to the students. Considering this, we expect that this research may assist in the decision making process and in proposing reflections about the evaluation dynamics that are carried out in this school.